Exploring the role of CITED transcriptional regulators in the control of macrophage polarization - Wiggins, Derek A.; Maxwell, Jack N.; Nelson, David E. (Frontiers in Immunology, 2024)
Macrophages are tissue resident innate phagocytic cells that take on contrasting phenotypes, or polarization states, in response to the changing combination of microbial and cytokine signals at sites of infection. During the opening stages of an infection, macrophages adopt the proinflammatory, highly antimicrobial M1 state, later shifting to an anti-inflammatory, pro-tissue repair M2 state as the infection resolves. The changes in gene expression underlying these transitions are primarily governed by nuclear factor kappaB (NF-κB), Janus kinase (JAK)/signal transducer and activation of transcription (STAT), and hypoxia-inducible factor 1 (HIF1) transcription factors, the activity of which must be carefully controlled to ensure an effective yet spatially and temporally restricted inflammatory response. While much of this control is provided by pathway-specific feedback loops, recent work has shown that the transcriptional co-regulators of the CBP/p300-interacting transactivator with glutamic acid/aspartic acid-rich carboxy-terminal domain (CITED) family serve as common controllers for these pathways. In this review, we describe how CITED proteins regulate polarization-associated gene expression changes by controlling the ability of transcription factors to form chromatin complexes with the histone acetyltransferase, CBP/p300. We will also cover how differences in the interactions between CITED1 and 2 with CBP/p300 drive their contrasting effects on pro-inflammatory gene expression.